Effect of the litter material on drinking water quality in broiler production - Garcia, RG (2010)
Considering the importance of drinking water and its effect on broiler performance, drinking water quality was studied using six different litter materials. The presence of coliform bacteria and Escherichia coli was investigated. The following litter materials were used in the trial: wood shavings, rice husks, chopped Napier grass (Pennisetum pupureum), 50% sugarcane bagasse (Saccharum L.) + 50% wood shavings, 50% sugarcane bagasse (Saccharum L.) + 50% rice husks, and plain sugarcane bagasse (Saccharum L.). A number of 1620 Ross® one-day-old chicks were reared in 54 pens measuring 4.5 m² each, equipped with a bell drinker and a tube feeder. Water samples were collected in sterile tubes on days 28 and 42 of the rearing period, and submitted to the laboratory for analyses. Microbiological data were organized by classes expressed in a logarithm scale, where the lowest contamination corresponds to class 1 and the highest contamination to class 4. Results showed that total coliform contamination was higher on day 28 than in the end of the rearing period, and that E. coli presence was detected during both analyzed periods. The litter materials that presented lower degree of water contamination, predominantly class 1, were sugarcane bagasse and 50% of sugarcane bagasse and 50% of rice husks.